Exploring Recent Trends in Agricultural Economics with a Focus on Agritech and Agribusiness - M. Aris Pujiyanto; Ernes Septina Azizi; Winda Widyastuti; Loso Judijanto (West Science Interdisciplinary Studies, 2023)
This research presents a comprehensive bibliometric analysis of current trends in agricultural economics with a specific emphasis on agritech and agribusiness. Leveraging advanced bibliometric tools, the study explores co-authorship networks, citation patterns, and thematic clusters within the scholarly literature. Key findings highlight influential authors, seminal publications, and emerging themes. The analysis sheds light on the evolving landscape of agricultural economics, emphasizing the transformative influences of technology and evolving business models. The results contribute to a nuanced understanding of the interdisciplinary nature of agricultural economics, offering valuable insights for researchers, policymakers, and practitioners navigating the complexities of modern agriculture.